Celestial Climate Driver: A Perspective from Four Billion Years of the Carbon Cycle - Veizer, Ján (Geoscience Canada)

(untitled) (The Geological Association of Canada, 2005)
SUMMARY The standard explanation for vagaries of our climate, championed by the IPCC (Intergovernmental Panel on Climate Change), is that greenhouse gases, particularly carbon dioxide, are its principal driver. Recently, an alternative model that the sun is the principal driver was revived by a host of empirical observations. Neither atmospheric carbon dioxide nor solar variability can alone explain the magnitude of the observed temperature increase over the last century of about 0.6°C. Therefore, an amplifier is required. In the general climate models (GCM), the bulk of the calculated temperature increase is attributed to "positive water vapour feedback". In the sun-driven alternative, it may be the cosmic ray flux (CRF), energetic particles that hit the atmosphere, potentially generating cloud condensation nuclei (CCN). Clouds then cool, act as a mirror and reflect the solar energy back into space. The intensity of CRF reaching the earth depends on the intensity of the solar (and terrestrial) magnetic field that acts as a shield against cosmic rays, and it is this shield that is, in turn, modulated by solar activity. Cosmic rays, in addition to CCN, also generate the so-called cosmogenic nuclides, such as beryllium-10, carbon-14 and chlorine-36. These can serve as indirect proxies for solar activity and can be measured e.g., in ancient sediments, trees, and shells. Other proxies, such as oxygen and hydrogen isotopes can reflect past temperatures, carbon isotopes levels of carbon dioxide, boron isotopes the acidity of ancient oceans, etc. Comparison of temperature records from geological and instrumental archives with the trends for these proxies may enable us to decide which one of the two alternatives was, and potentially is, primarily responsible for climate variability. This, in turn, should enable us to devise appropriate countermeasures for amelioration of human impact on air quality and climate.